Host Cell Rab GTPases in Hepatitis B Virus Infection - Zeyen, Lisa; Prange, Reinhild (Frontiers in Cell and Developmental Biology, 2018)
Hepatitis B virus (HBV) is a leading cause of liver disease and is presently estimated to infect more than 250 million humans. The extremely successful spread of this virus among the human population is explained by its effective transmission strategies and its manifold particle types, including virions, empty envelopes and naked capsids. Due to its tiny genome, HBV depends on cellular machineries to thrive in infected hepatocytes. To enter, traverse and exit the cell, HBV exploits host membrane trafficking pathways, including intracellular highways directed by Rab GTPases. Here, we review recent discoveries focused on how HBV co-opts and perturbs host Rab GTPase functions with an emphasis on Rab7A- and Rab33B-mediated trafficking pathways. Rab7A plays bidirectional roles in the viral life cycle, as it promotes the endocytic uptake of HBV in early stages, but restricts exocytic virion release in late stages. In intermediate stages of HBV propagation, Rab33B is needed to guide the assembly of replicative progeny nucleocapsids. Rab33B acts together with its Atg5-12/16L1 effector, a protein complex required for autophagosome formation, suggesting the concept that HBV exploits this Rab/effector complex as an assembly scaffold and machine. We also discuss whether Rab-directed trafficking pathways engaged by HBV may be applicable to other virus families. Identification of overlapping Rab functions may offer new chances to develop broad-spectrum host-targeted antiviral strategies.